GENDER, TAX KNOWLEDGE, AND COMPLIANCE AMONG SELF-EMPLOYED WORKERS IN LAGOS, NIGERIA - Azaka, Lilian (African Journal of Social and Behavioural Sciences, 2024)
This study investigates the relationship between gender, tax knowledge, and tax compliance among self-employed workers in Nigeria. The study employed a quantitative approach, collecting data through surveys administered to 129 self-employed individuals in Lagos, Nigeria. Statistical analysis, including t-test, correlation and regression analysis, was conducted to examine the relationships between gender, tax knowledge, and tax compliance. The findings revealed no significant gender differences in tax compliance and tax knowledge among self-employed workers in Nigeria. The study further explores possible reasons for this unexpected result, considering factors such as equal access to education, cultural norms, tax policies, and economic conditions. Additionally, the research confirms a positive relationship between tax knowledge and tax compliance. Individuals with a higher level of tax knowledge tend to exhibit greater tax compliance, reinforcing the importance of tax education and awareness campaigns in promoting voluntary compliance. These findings underscore the need for tailored tax policies and educational initiatives that consider the unique socio-economic context of Nigeria. In conclusion, this study contributes valuable insights into the dynamics of gender, tax knowledge, and tax compliance among self-employed workers in Nigeria. The absence of gender differences in tax compliance challenges conventional assumptions and highlights the need for context-specific research in tax compliance. Moreover, the positive association between tax knowledge and compliance underscores the importance of educational efforts to enhance tax literacy and ultimately improve voluntary compliance in Nigeria's self- employed sector.